2022
DOI: 10.3389/fnint.2021.726321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Structural Differences in Delusions Across Diagnoses: A Systematic Review

Abstract: Delusions are marked, fixed beliefs that are incongruent with reality. Delusions, with comorbid hallucinations, are a hallmark of certain psychotic disorders (e.g., schizophrenia). Delusions can present transdiagnostically, in neurodegenerative (e.g., Alzheimer's disease and fronto-temporal dementia), nervous system disorders (e.g., Parkinson's disease) and across other psychiatric disorders (e.g., bipolar disorder). The burden of delusions is severe and understanding the heterogeneity of delusions may delinea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…Bilateral reductions in volume of the claustrum have been found in patients with both schizophrenia and depression, but are largely confounded by chronic medication use (Bernstein et al, 2016). Decreases in gray matter volume of the left claustrum have been correlated with delusions in both Alzheimer's Disease and schizophrenia (Rootes-Murdy et al, 2022). Lesions to the claustrum have been implicated in a number of case studies where patients develop delusions and/or seizures (Milardi et al, 2015;Patru and Reser, 2015), but these case studies often include adjacent structures making it difficult to infer the claustrum-specific function.…”
Section: The Claustrum: Worth Further Explorationmentioning
confidence: 99%
“…Bilateral reductions in volume of the claustrum have been found in patients with both schizophrenia and depression, but are largely confounded by chronic medication use (Bernstein et al, 2016). Decreases in gray matter volume of the left claustrum have been correlated with delusions in both Alzheimer's Disease and schizophrenia (Rootes-Murdy et al, 2022). Lesions to the claustrum have been implicated in a number of case studies where patients develop delusions and/or seizures (Milardi et al, 2015;Patru and Reser, 2015), but these case studies often include adjacent structures making it difficult to infer the claustrum-specific function.…”
Section: The Claustrum: Worth Further Explorationmentioning
confidence: 99%
“…Thalamus involvement in psychosis is, indeed, well-established and supported by fMRI studies (63). Finally, a systematic review on neural underpinnings of delusional symptoms in schizophrenia and Alzheimer's disease patients reported lateralized findings of gray matter reductions in the left claustrum (64), reinforcing the notion of left hemisphere involvement in the genesis of psychotic symptoms. While these observations align with the hypothesis of left hemisphere involvement in psychotic symptoms in some populations, a systematic review in patients with post-stroke psychosis found that right hemisphere lesions were more common (in around 40% of the cases, against 11% with a different pattern of lesions).…”
Section: Discussionmentioning
confidence: 80%
“…However, given the symptom variation within each disorder, we hypothesized that there may be subclusters within and across each disorder, that may help distinguish the underlying neural networks involved in each disorder. For example, delusions in bipolar disorder, were associated with gray matter reductions largely in the frontal cortex and amygdala and SZ showed similar patterns with additional contributions from subcortical regions (Rootes-Murdy et al, 2022). Within individuals with SZ, a symptom phenotype consisting of higher delusional symptoms, suspiciousness, hallucinations, and anxiety [measured from the Positive and Negative Syndrome Scale (PANSS); (Kay et al, 1987)] was associated with a covarying pattern of lower GM concentration in inferior temporal gyri and fusiform gyri and higher GM concentration in the sensorimotor cortex (Mennigen et al, 2019).…”
Section: Introductionmentioning
confidence: 91%